It is currently 18 Nov 2017, 16:06

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# Each person attending a fund-raising party for a certain

Author Message
Manager
Joined: 21 Mar 2007
Posts: 72

Kudos [?]: 108 [0], given: 0

Each person attending a fund-raising party for a certain [#permalink]

### Show Tags

07 Mar 2008, 04:15
00:00

Difficulty:

(N/A)

Question Stats:

0% (00:00) correct 0% (00:00) wrong based on 0 sessions

### HideShow timer Statistics

This topic is locked. If you want to discuss this question please re-post it in the respective forum.

Each person attending a fund-raising party for a certain club was charged the same admission fee. How many people attended the party?

Kudos [?]: 108 [0], given: 0

Manager
Joined: 31 Oct 2007
Posts: 112

Kudos [?]: 73 [1], given: 0

Location: Frankfurt, Germany

### Show Tags

07 Mar 2008, 04:33
1
KUDOS
In this question, we are looking for the no. of people.

Statements 1 and 2 alone are not sufficient because by itself, each statement has 3 variables for you to solve. 1st variable, the admission fee, 2nd variable the no of people attended and 3rd the total amount. Neither statement alone allows you to solve.

--

If this question is a PS question, the working as follows:
Let x be the admission fee per person
Let y be the no of person
Let z be the total admission fees

Statement 1:
(x - 0.75) * (y + 100) = z

Statment 2:
(x + 1.50) * (y - 100) = z

Thus, statement 1 = statment 2

(x - 0.75) * (y + 100) = (x + 1.50) * (y - 100)
=> xy + 100x - 0.75y -75 = xy - 100x + 1.50y - 150
=> - 0.75y - 75 = 1.50y - 150
=> 2.25y = 75
=> y = 75/2.25
=> ~33ppl
_________________

Jimmy Low, Frankfurt, Germany
Blog: http://mytrainmaster.wordpress.com
GMAT Malaysia: http://gmatmalaysia.blogspot.com

Last edited by jimmylow on 07 Mar 2008, 22:16, edited 1 time in total.

Kudos [?]: 73 [1], given: 0

Manager
Joined: 21 Mar 2007
Posts: 72

Kudos [?]: 108 [0], given: 0

### Show Tags

12 Mar 2008, 04:59
jimmylow wrote:
In this question, we are looking for the no. of people.

Statements 1 and 2 alone are not sufficient because by itself, each statement has 3 variables for you to solve. 1st variable, the admission fee, 2nd variable the no of people attended and 3rd the total amount. Neither statement alone allows you to solve.

--

If this question is a PS question, the working as follows:
Let x be the admission fee per person
Let y be the no of person
Let z be the total admission fees

Statement 1:
(x - 0.75) * (y + 100) = z

Statment 2:
(x + 1.50) * (y - 100) = z

Thus, statement 1 = statment 2

(x - 0.75) * (y + 100) = (x + 1.50) * (y - 100)
=> xy + 100x - 0.75y -75 = xy - 100x + 1.50y - 150
=> - 0.75y - 75 = 1.50y - 150
=> 2.25y = 75
=> y = 75/2.25
=> ~33ppl

What happens to the 200x that appears when the -100x from the right is added on to the 100x on the left?

Kudos [?]: 108 [0], given: 0

CEO
Joined: 29 Mar 2007
Posts: 2553

Kudos [?]: 527 [0], given: 0

### Show Tags

12 Mar 2008, 05:16
japped187 wrote:
jimmylow wrote:
In this question, we are looking for the no. of people.

Statements 1 and 2 alone are not sufficient because by itself, each statement has 3 variables for you to solve. 1st variable, the admission fee, 2nd variable the no of people attended and 3rd the total amount. Neither statement alone allows you to solve.

--

If this question is a PS question, the working as follows:
Let x be the admission fee per person
Let y be the no of person
Let z be the total admission fees

Statement 1:
(x - 0.75) * (y + 100) = z

Statment 2:
(x + 1.50) * (y - 100) = z

Thus, statement 1 = statment 2

(x - 0.75) * (y + 100) = (x + 1.50) * (y - 100)
=> xy + 100x - 0.75y -75 = xy - 100x + 1.50y - 150
=> - 0.75y - 75 = 1.50y - 150
=> 2.25y = 75
=> y = 75/2.25
=> ~33ppl

What happens to the 200x that appears when the -100x from the right is added on to the 100x on the left?

Yes what happened to that 200x...

I get E for this problem b/c we are left with 200x+75=2.25y

Kudos [?]: 527 [0], given: 0

Manager
Joined: 11 Apr 2007
Posts: 143

Kudos [?]: 45 [0], given: 0

### Show Tags

12 Mar 2008, 07:19
That's not how I did it.
Since in the question we have that x*y=z
(1) (x-0.75)*(y+100)=z => (x-0.75)*(y+100)=xy from here we remain with 100x-0.75y=75 not suff
(2) (x+1.50)*(y-100)=z => (x+1.50)*(y-100)=xy from here we remain with -100x+1.50y=150 not suff

(1)(2) we have 100x-0.75y=75
-100x+1.50y=150
If we add these 2 equations we have 0.75y=225, y =300
100x-225=75, x=3
So sufficient C

Kudos [?]: 45 [0], given: 0

Re: GMAT Prep DS   [#permalink] 12 Mar 2008, 07:19
Display posts from previous: Sort by